Peeking into the bleak midwinter: Investigating nonbreeding strategies of Gentoo Penguins using a camera network - Black, Caitlin; Raya Rey, Andrea Nélida; Hart, Tom (The Auk)
When monitoring species with extensive ranges in harsh climates, comprehensive studies across a species' range are both logistically and technically challenging and therefore rare. Such scarcity in data collection is particularly true in the polar regions where sea ice and weather constraints prevent widespread access to sites for much of the year, specifically during winter. Penguins (Spheniscidae) show large variations in winter strategies with many species migrating long distances while others are distinctly sedentary, remaining at the colony year-round. However, in some species, their attendance at the breeding site during the nonbreeding winter period depends greatly on the colony location and environmental factors. Here we aim to examine fluctuations in winter attendance at the breeding site in Gentoo Penguins (Pygoscelis papua) along a latitudinal gradient of 7 sites, ranging from Martillo Island, a colony in Argentina, to Petermann Island, a colony located toward the southern edge of the species' range on the Western Antarctic Peninsula. We use an established network of cameras to observe winter populations of penguins across a large latitudinal gradient. This study provides the first evidence of across-year variation in Gentoo Penguin nonbreeding attendance at the breeding site. We found that both temporal and spatial factors drive winter attendance in this species with distinct patterns between years and colony locations, particularly at the edges of its range. Additionally, environmental and temporal factors, including sea ice extent directly offshore and photoperiod, appear to dictate Gentoo Penguin winter attendance across their range. As Gentoo Penguins are neither sedentary nor migratory during the nonbreeding period, understanding patterns in winter site occupation across time and space provides insight into half of the species' annual cycle and has important implications in the face of changes in climate, direct human disturbance, and fisheries activities. Lors du suivi d'espèces comportant ...